Pharmacokinetics of Saquinavir, Atazanavir, and Ritonavir in a Twice-Daily Boosted Double-Protease Inhibitor Regimen - von Hentig, Nils (American Society for Microbiology, 2007)
The objective of this study was to evaluate the pharmacokinetics of atazanavir (ATV), saquinavir (SQV), and ritonavir (RTV) in a boosted double-protease inhibitor (PI) therapy regimen without reverse transcriptase inhibitors (RTIs). The study design was as follows. Patients with limited RTI options received a PI combination of 300/100 mg ATV/RTV once daily and 1,000 mg SQV twice daily (group 1; n = 49) without RTI comedication. The results were compared to the plasma concentrations of PIs of patients taking either 300 mg ATV/100 mg RTV once daily plus RTIs (group 2; n = 72) or patients taking 1,000 mg SQV/100 mg RTV plus RTIs (group 3; n = 90). The study methods were as follows. Patients were given a 12/24-h pharmacokinetic assessment at steady state. Drug concentrations were measured by liquid chromatography-tandem mass spectrometry. The minimum and maximum concentrations (C(min) and C(max)), area under the concentration-time curve under steady-state conditions (AUC(ss)), elimination half-life, time of maximum concentration and lag time were subject to statistical analysis. The results show that patients treated with ATV/SQV/RTV exhibited significantly high SQV concentrations and moderate enhancement of the AUC(ss) of ATV in comparison to those of patients of the control groups: for SQV in groups 1 and 3, the geometric mean (GM) of the AUC(ss) was 22,794 versus 15,759 ng·h/ml (GM ratio [GMR] = 1.45; P < 0.05), the GM of the C(max) was 3,257 versus 2,331 ng/ml (GMR = 1.40; P < 0.05), and the GM of the C(min) was 438 versus 437 ng/ml (GMR = 1.00); for ATV in groups 1 and 2, the GM of the AUC(ss) was 39,154 versus 33,626 ng·h/ml (GMR = 1.16), the GM of the C(max) was 3,488 versus 2,924 ng/ml (GMR = 1.20), and the GM of the C(min) was 515 versus 428 ng/ml (GMR = 1.21). RTV levels were comparable for all groups. A subgroup analysis detected only marginal differences in ATV plasma exposure if combined with tenofovir-disoproxilfumarate and without it. We conclude that our pharmacokinetic results support the use of a boosted double-PI regimen of ATV/SQV/RTV as a treatment option for patients who need antiretroviral therapy without RTIs.